2022
DOI: 10.7759/cureus.28710
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Use of the HPV Vaccine in the Prevention of Cervical Cancer

Abstract: The main risk factor for invasive cervical carcinoma is persistent infection by the high-risk human papillomavirus (HPV). HPV is the most prevalent sexually transmitted infection (STI) and has been linked to 15 different cancers. Cervical cancer is one of the most frequent cancers among women, particularly in resource-limited countries. Cervical cancer is an HPV disease with the highest worldwide burden in resource-limited nations. With improved medical care and nationwide screening programmes, the mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The HPV is a pervasive viral infection that poses a significant global public health concern due to its association with CC, among other malignancies [ 25 ].Vaccination against HPV has proven to be a powerful preventive measure against these potentially life-threatening diseases [ 26 ]. However, adequate awareness and understanding of the HPV vaccine, particularly among parents with daughters, are paramount for the successful implementation and uptake of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The HPV is a pervasive viral infection that poses a significant global public health concern due to its association with CC, among other malignancies [ 25 ].Vaccination against HPV has proven to be a powerful preventive measure against these potentially life-threatening diseases [ 26 ]. However, adequate awareness and understanding of the HPV vaccine, particularly among parents with daughters, are paramount for the successful implementation and uptake of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Groundbreaking studies demonstrate its safety and effectiveness against a gamut of potentially life-altering HPV-related health conditions. From cervical cancer to many other perilous maladies, the vaccine is an epoch-making beacon of hope and renewal for the female populace embroiled in this battle [31,32].…”
Section: I) Hpv Vaccinementioning
confidence: 99%
“…Embracing this paradigm shift, the American Cancer Society now recommends HPV testing as the primary screening test for females aged 25 and above. Furthermore, research suggests that this screening system can almost completely eradicate cervical cancer in low-income countries, making it the key for women to realize a life without such a fearful disease [31].…”
Section: Iv) Breast Cancer Screeningmentioning
confidence: 99%
“…HPV messages framed in the context of cancer prevention could be an effective way to educate young adult men and increase their perceived risk for HPV. Similar strategies have been effective for motivating young adult women and parents of adolescent girls to get the vaccine ( Pathak et al, 2022 ). For example, a cervical cancer communication campaign for college women reported that messages designed to increase awareness of susceptibility of HPV and acceptability of the HPV vaccine influenced participants’ self-reported vaccination likelihood ( Sundstrom et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%